Pembuatan vulkanisat ban dalam dengan bahan pengisi arang aktif kayu bangkirai - Herminiwati, Herminiwati; Darmadji, Purnama; Supranto, Supranto (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2003)
The objective of this research was to study the preparation of vulcanized rubber inner tube for motorcycles. Activated carbon of bangkirai wood and carbon black N330 were utilized as filler either separately formulated or combination. The ratio of activated carbon and carbon black were 25/ 0; 18/75/6,25; 12,5/12,5; 6,25/18,75 and 0,25 respectively. In wood processing, only about 60% of wood is converted to end product, with some of 30% of the rest is converted to organic solid waste. This organic solid waste needs to be handled or converted to some more usefull product such as carbon rubber filler. The filler was prepared by carbonization process at temperature 4500C for one hour and activation process with NaCl 4 % for twenty four hours, followed by pyrolysis at temperature 5000C for one hour. Filler were milled and sieved by 400 mesh siefter. The vulcanized rubber inner tube was tested for its physical properties according to SNI 06-1542-1984. The research showed that a filler combination of activated carbon of bangkirai wood and carbon black in comparison of 6,25/18,75 could meet the requirements of SNI 06-1542-1984 in tensile strength, elongation at break, 300% modulus, hardness, density, and 200% permanent set. Keywords : filler, activated carbon, bangkirai wood, inner tube.